PERLINDUNGAN HUKUM KONSUMEN ATAS PENJUALAN ALBUM KPOP PALSU DI E-COMMERCE - Azmilatun Nafisah; Abdullah Fikri (Universitas Labuhanbatu, 2026)
The rapid advancement of information technology has accelerated the growth of electronic commerce (e-commerce) as a trading platform that offers greater convenience and efficiency for consumers. However, this development has also increased the risk of fraudulent practices in electronic transactions, particularly those involving discrepancies between the products advertised and those actually received by consumers. This situation raises concerns regarding the effectiveness of legal protection afforded to consumers in e-commerce transactions. This study aims to analyze the legal protection available to consumers who become victims of counterfeit or non-conforming products sold through e-commerce platforms and to examine the effectiveness of the implementation of Law Number 8 of 1999 concerning Consumer Protection in ensuring legal certainty. This research employs a normative legal method using statutory and conceptual approaches. Primary and secondary legal materials were analyzed qualitatively through legal interpretation of legislation governing consumer protection in electronic transactions. The findings indicate that consumer legal protection has not yet been fully effective due to the continued circulation of counterfeit products, the limited accountability of business actors, and the inadequacy of dispute resolution mechanisms and regulatory oversight in electronic commerce. This study concludes that strengthening regulatory supervision, enhancing the accountability of e-commerce platform providers and business actors, and optimizing the implementation of consumer protection legislation are essential to improving legal certainty and ensuring more effective legal protection for consumers in the digital marketplace.Keywords: E-commerce; Consumer Protection; Fraud; Legal Protection; Electronic Transactions.